Objects of Resilience: Plush Perspectives on Pandemic Toy Play in Finland - Heljakka Katriina (Open book publishers, 2025)
This chapter addresses plush perspectives on pandemic toy play by positioning the #teddychallenge as an example of creative intergenerational and continuous play which developed into an international phenomenon in the early stages of the Covid-19 pandemic. In March 2020, teddy bears and other plush toys were brought to the windows in New Zealand, Australia, UK, Europe and North America. The world’s most popular character toy sat in the windows, often holding hands or giving hugs to other toy friends, depicting the longing for human closeness with its gestures. As a form of hybrid and screen-based play, the plush characters enabled communication between players separated by the pandemic. The chapter presents a three-partite study investigating the role of soft toys in pandemic toy play during three phases between 2020-2021, including participatory observation, analyses of media articles, photo-play (toy photography), and interview material collected in three phases. The plush toys depicted playful human reactions to the health crises—first, in the occurrences of the global #teddychallenge, second, as part of the free toy play of interviewees based in the UK, Finland and Singapore, and third, in the photo-play of the replaying of the challenge introduced by a regional Finnish news media. The findings suggest the capacity of plush characters to function as objects of resilience on both a solitary and social level. From personal protectors and companions used in solitary play, the plush evolved into toys used socially for ludounity—playing for the common good—as they were employed as part of intergenerational play and to channel optimism and future-orientedness.
Play in a Covid Frame: Everyday Pandemic Creativity in a Time of Isolation